Utfodra hundar och katter med kött- eller växtbaserat foder - Sundström, Sara (2022)
Dogs and cats are the most common pets in the world and today’s pet food market offers a wide range of different kind of products. One of the most popular pet food trends is to feed your dog or cat a meat-based raw food because it assumes to be a more natural diet for them. A rather new trend among pet owners is to feed your dog or cat with a plant-based diet even though they are predators, and therefore their diet should naturally include meat. Previous scientific studies show the risks with meat- and plant-based diets both being nutritionally unbalanced and for that reason should neither of them be a recommended diet for your pet. However, there are few studies describing the potential benefits with feeding your dog and cat with a meat- or plant-based diet. The aim of this paper is to determine the current benefits and disadvantages with the two different types of diets and compare them if whether one or the other is more appropriate for your carnivorous pet. The paper does also include a comparison between different brands of meat- and plant-based diets for dogs and cats with the aim to examine if the products meet the recommended nutritional guidelines for dogs and cats. The main results shows that there are more disadvantages with meat based diet, for example bacterial contamination, nutritional diseases, and higher climate impact. Plant based food seems to have a lower climate impact but is often nutritionally unbalanced which increases the risk for the animals to develop diseases. The number of studies is limited and therefore more studies about the effects of feeding your pet with a meat- or plant based diet are necessary.